Note From Baduy About Learning To Sustain The Ecology Of The Baduy Community - M Noor Fajar Al Arif Fitriana; Ahmad Fauzi (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
The development of environmental law in Indonesian society which is influenced by the way of thinking of the west that leads to the industrialists and consumptive headed at the thought of anti-ecological, we have to learn to one of the tribes that exist in Banten, the Baduy community, a tribe that is still firmly uphold customary law as the foundation of living. Baduy is one of the indigenous communities, which until now still live a life day-to-day based on the law that they have. This research was included in a type of qualitative research that is descriptive, is research that aims to describe something problems in certain areas or at certain times. This research method is used to describe systematically the facts or characteristics of a specific population or a particular field, in this field are actual and carefully. This method focuses on the observation and experience of nature. This study also uses primary and secondary data sources, which are analyzed using a qualitative method,with data collection techniques the Study of Literature and Field Studies to the Baduy community, the interview was conducted to the speaker to get accurate data about the conditions and the realities on the baduy community. The results of the research are the baduy apply customary law in the form of pikukuh karuhun, if we observe how the Baduy community in maintaining the ecology of the environment both in the system of agriculture and preservation of the forest in accordance with the laws of the environment in the modern meaning. but we can take the values that they apply to the Baduy community. Need for synergy between the government, employers and the community in preserving the environment. It's time the government issued a policy to concrete to protect environmental sustainability with the implementation of value of local wisdom because it contained the value of human interaction and the environment.